Study on Seed Size Variation in Soybean (Glycine max L. Merr.) and its Correlation with Yield - Ray, D. Datta; Sen, S.; Bhattacharyya, P. K.; Bhattacharyya, S. (International Journal of Economic Plants, 2022)
The present research aimed during June-September, 2016 at the RRS (NAZ) farm, BCKV, Gayeshpur, Nadia, West Bengal, India to select promising soybean genotypes based on seed size and yield. Twenty-five soybean genotypes were grown and evaluated for the seed area (mm2), pods plant-1, seeds pod-1, 100 seed weight (g), and seed yield plant-1. Measurement of seed size was done in terms of seed area (mm2) using BioVis® surface area meter. The study revealed significant genetic variability in terms of seed size among the genotypes. The average seed area (mm2) along with yield and yield attributing characters were compared. The average seed size ranged from 31.94-51.72 mm2 while seed yield plant-1 had a range of 20.9-45.2 g. The genotype PS1042 was found to be very bold seed having a seed area of 51.72 mm2 along with PK416 and PK564, which showed 51.20 and 50.09 mm2 seed area respectively.On the contrary, JS9752 was categorized as the genotype with the smallest seed size; 31.94 mm 2 along with PK 327 (33.17 mm2)). Seed size exhibited a significant positive correlation with 100 seed weight and seed yield plant-1. The regression curves also revealed the pattern of contribution seed area had on yield and the yield parameters. The results of this study indicated seed size as an important parameter to be considered as one of the most reliable selection indices while breeding for high yielding soybean varieties.